Monetization in Low- and Middle-Income Countries - Kinoshita, Noriaki (IMF Working Papers; Working Paper ;, 2012)
The degree of an economy's monetization, which has an important implication on economic growth, can be affected by the conduct of monetary policy, financial sector reform, and episodes of financial crises. The paper finds that monetization--measured by the ratio of broad money to nominal GDP-- in low- to middle-income countries is significantly correlated with per-capita GDP, real interest rates, and financial sector reform. It suggests that maintaining an upward momentum in monetization can be an important policy objective, particularly for low-income countries, and that monetary and financial sector policies need to be conducive to enhancing monetization.